FORMULATION AND EVALUATION OF IBUPROFEN GASTRO-RETENTIVE FLOATING TABLETS - C Shaikh, Saddam; Sanap, Dnyaneshwar; Bhusari, Dipak V; Jain, Shirish; Kochar, Pooja P; Sanchati, Vikram N (Universal Journal of Pharmaceutical Research, 2018)
Objective: The objective of the present study was to formulate the gastro-retentive floating tablets containing Ibuprofen, which would remain in stomach and/or upper part of GIT for prolonged period of time. Floating systems have low bulk density so that they can float on the gastric juice in the stomach. Ibuprofen is an anti inflammatory drug. Methods: On trial and error basis formulation design was done. Four different batches of floating tablets of Ibuprofen were prepared using HPMC, Xanthan gum, and gas generating agent sodium bicarbonate and citric acid. The tablets were characterized for the pre and post compression parameters such as friability, hardness, thickness, drug content, weight variation, in-vitro buoyancy studies and 13 hrs in-vitro drug release studies and the results were within the limits. Results: There was no interaction found in between drug and other ingredients. Maximum release was shown by formulation of batch F4 (47.38%), and minimum by the formulations of batch F2 (34.46%) in the duration of 13 hrs. Conclusion: From the results obtained, it was concluded that the optimized formulation F4 desired drug release properties and floating behavior. Peer Review History: Received 21 May 2018; Revised 6 July; Accepted 10 September; Available online 15 September 2018 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Heba M. Abd El-Azim , Damanhour University, Egypt, h_m_abdelazim@hotmail.com Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com